Immune-phenotyping and transcriptomic profiling of blood monocytes from patients with breast cancer under neoadjuvant chemotherapy - M. R. Patysheva; M. N. Stakheyeva; E. S. Grigoryeva; P. S. Iamshchikov; I. V. Larionova; А. A. Budnickya; N. A. Tarabanovskaya; N. V. Cherdyntseva; J. G. Kzhyshkowska (Успехи молекулярной онкологии, 2024)
Introduction. Chemotherapy is a common treatment for breast cancer. Chemotherapeutic drugs effect blood monocytes, which are major contributors to cancer pathogenesis. However, to date, pro-tumor or anti-tumor programming by chemotherapy of monocytes is controversial.Aim. To characterize changes in phenotypic and transcriptomic profiles of monocytes of breast cancer patients before and after chemotherapeutic treatment.Materials and methods. In a cohort of 50 breast cancer patients, monocyte populations were identified based on their expression of CD14, CD16, CD163, and HLA-DR evaluated by flow cytometry before and after neoadjuvant chemotherapy. Bulk RNA sequencing was adopted to explore the transcriptomic profile of CD14+ monocytes before and after treatment. After treatment, we observed an increase in the activity of signaling pathways related to lipid metabolism and intracellular transport of vesicles from the endoplasmic reticulum, against the background of a decreased response to exposure to interferon γ and interferon α, and foreign molecules (exogenous nucleic acids, viruses and bacteria).Results. In breast cancer patients, neoadjuvant chemotherapy decreased in CD14+16+HLA-DR+ monocytes. Under cytostatic treatment, increased gene expression of MGLL, NR4A2, UCK1, YOD1, ABCA2, PAPSS2, ATP10 (log2FoldChange ≥0.8; false discovery rate (FDR) ≤0.01) and decreased gene expression of KPNA2, ERCC4, JAGN1, RUBCNL, SMYD4, B3GALT4 (log2FoldChange ≥0.8; FDR ≤0.01) were observed in monocytes of patients. Using discriminant analysis, the relative numbers of CD14+16–, CD14+16+, CD14-16+, CD14+16-HLA-DR+, CD14+16+HLA-DR+ and CD14–16+HLA-DR+ monocytes in the blood were found to be valuable in predicting response to neoadjuvant chemotherapy.Conclusion. Thus, association of blood monocytes with chemotherapeutic treatment in breast cancer was revealed.